First ecological report of bat diversity present in sierra de navachiste protected area, Sinaloa, Mexico. - Aguilar-Romero, R. J.; Escobedo-Bonilla, C. M.; Martínez-Álvarez, I. G.; Ley-Quiñónez, C. P.; Hart, C. E.; Zavala-Félix, K. A.; Leal-Moreno, R.; Suzán, G.; Aguirre, A. A.; Zavala-Norzagaray, A. A. (Revista Bio Ciencias, 2022)
In Mexico, studies on chiropters have reported the presence of eight families and a total of 138 species, of which seven families and 55 species are reported for the state of Sinaloa. However, the Sierra de Navachiste, México is a natural protected area of state jurisdiction registered as an area subject to Ecological Conservation. studies on bat populations in this area are scarce or nonexistent, resulting in their environmental needs, current threats and the impact they have at population level being unknown. Despite finding a low species richness (five species), caught two migratory species in Sierra de Navachiste: Mormoops megalophylla and Leptonycteris yerbabuenae. This last bat is included on the IUCN red list (International Union for the Conservation of Nature) as a "vulnerable" species, and in Mexico it is a "threatened" species. This bat is considered a key species within the ecosystem due to being the pollinator of the dominant columnar cacti as well as a distributor of its seeds though fruit consumption. This activity promotes the dispersal of these plants and maintains the structure and health of the ecosystem. Due to the importance of the Sierra Navachiste as a refuge for at least five bat species, including two migratory and one protected species, it is necessary to establish a management plan in order to protect the chiroptera community that depends on it.